PENGARUH AUDIT TENURE, AUDIT FEE, TEKANAN WAKTU, TEKANAN KLIEN DAN KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT PADA KAP SEMARANG - Yunike Nadya Pitaloka Santoso; Tarmizi Achmad (Diponegoro Journal of Accounting, 2019)
This research is aimed to examine the affect of audit tenure, audit fees, time pressure, client pressure and task complexity on audit quality. This research is conduted by auditor who worked on Public Accountant Firm at Semarang City. There are five hypotheses in this research, the affect of audit tenure, audit fees, time pressure, client pressure, and task complexity on audit quality. This research uses primary data that is obtained from distribution result of questionnaires to Public Accountant Firm at Semarang City. Purposive sampling method is used in this research. This research uses data analysis techniques with descriptive statistical tests, instrument testing, classic assumption tests, and hypothesis testing. The result of this research shows that audit tenure didn’t affect on audit quality. Audit fees affect on audit quality. Time pressure affects negatively on audit quality. Client pressure has significant positive effects on audit quality. Task complexity affects positively on audit quality.